6 - The Role of Older Persons in Uganda: Assessing Socio-demographic Determinants of Older Persons’ Value - Nzabona, Abel; Ntozi, James (Africa Development, 2021)
Extensive research has been conducted on diverse socio-demographic issues such as child and maternal mortality in Uganda but the contribution of older persons to their households and communities has been comparatively under-investigated. This article bridges the gap by discussing prevalence and determinants of the value of persons aged sixty and above in the country. Four rural districts were randomly selected while one urban area was purposively chosen in a cross-sectional study conducted from March to April 2012. An interviewer-administered questionnaire was used to collect data on 605 older persons. Engagement in income-generating activities, possession of indigenous knowledge, advice on behaviour norms, role played in social organizations, propagation of cultural norms, dispensing local medicine and providing childcare were all aspects of value studied. Using scaling technique, these eight variables were aggregated into a single total indicator of value, operationally defined as aggregate value. The variable was then dichotomized into low aggregate value and high aggregate value. Binary logistic regression was used to analyse socio-demographic factors predicting high aggregate value. Findings indicate that nearly four in ten older persons had high aggregate value. In comparison with persons of no education, those having primary and secondary or higher education were more likely to have high aggregate value. In comparison with persons who did not own land, those who owned land were more likely to have high aggregate value. Results further indicate that having out-migrated children predicted high aggregate value. In comparison with the Central region of the country, older persons living in the Western, Northern and Kampala regions were more likely to have high aggregate value. The findings have several implications including for the design of later-life socio-economic programmes, establishment of a special old age fund and increasing learner access and retention rates in the national education system.